2011
DOI: 10.1007/s10584-011-0314-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic impacts of climate-related changes to California agriculture

Abstract: California agriculture is driven by the interactions between technology, resources, and market demands. Future production is a balance between the rates of change in these variables and environmental factors including climate change. With tight statewide water supplies and agriculture being an important part of the California economy, quantifying the economic consequences of changes in these variables is important for addressing related policy questions. We estimate the economic effects of climate change on Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 19 publications
1
51
0
1
Order By: Relevance
“…The PMP considers the farmer's optimization process, allowing for a perfect calibration of area planted, for the full range of agricultural activities, avoiding the dependency between parameters and constraints. The approach followed in this paper is extensively used in agricultural economics due to its accuracy when the model calibration is based on a single base year (complemented with exogenous price elasticities) (Heckelei and Britz, 2005;Howitt et al, 2010;Medellín-Azuara et al, 2011).…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PMP considers the farmer's optimization process, allowing for a perfect calibration of area planted, for the full range of agricultural activities, avoiding the dependency between parameters and constraints. The approach followed in this paper is extensively used in agricultural economics due to its accuracy when the model calibration is based on a single base year (complemented with exogenous price elasticities) (Heckelei and Britz, 2005;Howitt et al, 2010;Medellín-Azuara et al, 2011).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Other applications include the estimation of the economic value of water and land (Howitt et al, 2001;Iglesias and Blanco, 2008;Medellín-Azuara et al, 2009;Kan et al, 2009), and climate change impacts (Henseler et al, 2009;Howitt et al, 2010;Medellín-Azuara et al, 2011;Howitt et al, 2012) (for reviews of other case studies see Heckelei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited and uncertain supply of both surface water and groundwater is an important constraint on California agriculture (Mukherjee and Schwabe 2014), and water availability will likely change under future climate due to changes in precipitation and evaporative demand. However, the exact patterns of changing water availability are difficult to predict, not only due to inherent uncertainties in climate modeling (CCTAG 2015) but also due to complexities of water policy in California (Joyce et al 2011). Medellin-Azuara et al (2011 concluded Bthe major effects of climate change on California agriculture are manifest through water shortages.Ŝ econd, the use of subjective temperature sensitivity metrics for each crop (on a scale of 1 to 4) prioritizes simplicity and ease of interpretation, but a single integer cannot fully describe a crop's climate response.…”
Section: Limitations Of This Approachmentioning
confidence: 99%
“…Agriculture largely rode out the drought by continuing to deplete the already vastly overdrafted groundwater, but at a cost of $590 million in that year alone. Statewide figures mask the uneven socioeconomic impacts of the drought, which fell disproportionately on agricultural areas south of the Sacramento/San Joaquin Bay Delta in the San Joaquin Valley [3][4][5].…”
Section: Introductionmentioning
confidence: 99%